Automatic Chakali Maker - Srivastava, Harshit; Sulla, Kartik; Jagtap, Srushti; Thorat, Anjali; Thakur, Aastha (International Journal of Recent Advances in Multidisciplinary Topics, 2023)
Automation is the control of machines and processes by autonomous frameworks through the utilize of various technologies which are based on computer program or robotics. Automation is presently a need within the food industry to address the desired levels of quality control, production speed, labor deficiencies and in general benefit. The proposed machine is related to food industry. It makes a difference to diminish the work fetched as well as time. It diminishes the work stack as well. We are attempting to manufacture a machine which can donate high speed with more precise shape of chakali. This machine has high proficiency to the generation rate as compared to manual and conventional process.